Physiological and Molecular Changes in Cherry Red Tobacco in Response to Iron Deficiency Stress - Liu, Fei; Zhang, Yihan; Pu, Xiaojun; Cai, Nan; Sui, Xueyi; Rengel, Zed; Chen, Qi; Song, Zhongbang (Frontiers in Plant Science, 2022)
The genotype CR60 is a spontaneous Cherry Red variant (containing granular red dapples on flue-cured leaves) of the Yunyan 87 (Y87) tobacco; it accumulates higher concentration of iron (Fe) in leaves than Y87, but the physiological differences between them remain largely unknown. We investigated the physiological and molecular mechanisms of CR60 in response to Fe deficiency under hydroponic conditions. Our results showed that no significant phenotypic difference between Y87 and CR60 was observed at optimal (40 μM) and high Fe (160 and 320 μM) concentrations. By contrast, CR60 exhibited higher tolerance to Fe deficiency (0 μM) than Y87, as shown by higher concentrations of chlorophyll in CR60 leaves after 21-day Fe deficiency stress. Transcriptome profiling coupled with RT-PCR analyses found that the expression of IRT1 and several genes associated with chlorophyll biosynthesis and photosynthesis (eg. PRO, GSA, FD1, PsbO and PC) was higher in CR60 than Y87. These results indicated that CR60 maintains sufficient Fe uptake, chlorophyll biosynthesis and photosynthetic rate when subjected to Fe starvation.